POLA PERGERAKAN KATAK BATU BERBINTIK HITAM (Staurois gutattus Gunther, 1859) DI GUNUNG POTENG KALIMANTAN BARAT - Jakaria, Mohamad; Junardi, Junardi; Riyandi, Riyandi (Jurnal Protobiont, 2020)
Movement patterns has been observed in black-spotted rock frog (Staurois gutattus). The aim of this study was to obtain data movement patterns. This research was conducted at Mountain Poteng, West Kalimantan. Data were analized graphically to explain the relationship between the used parameters. There are 20 individual frogs were observed for 24 hours by using a spool track, which consists of 10 males and females. Chi square test result values of alignment grooves conducted on 20 individual frogs were observed during the 24 hours of observation showed that the χ2 count < χ2 table with a value of (χ2 = 0,61 < 3,481, p = 0,05; Chi square test), it shows that the pattern of movement of male and female frogs do not stay away from the starting point of observation.